Sharp Bounds for the Weighted Hölder Mean of the Zero-Balanced Generalized Complete Elliptic Integrals - Zhao, Tie-Hong; He, Zai-Yin; Chu, Yu-Ming (Computational methods and function theory, 2021)
In the article, we present the best possible bounds for the weighted Hölder mean of the zero-balanced generalized complete elliptic integrals of the first and second kinds, which are the generalizations of previous results for complete p -elliptic integrals.